Trade Measures for Regulating Transboundary Movement of Electronic Waste - Christian, Gideon Emcee (Utrecht Journal of International and European Law, 2017)
International trade in used electrical and electronics equipment (UEEE) provides an avenue for socio-economic development in the developing world and also serves as a conduit for transboundary dumping of waste electrical and electronic equipment (WEEE) also referred to as electronic waste or e-waste. The latter problem arises from the absence of a regulatory framework for differentiating between functional UEEE and junk e-waste. This has resulted in both functional UEEE and junk e-waste being concurrently shipped to developing countries under the guise of international trade in used electronics. Dealing with these problems will require effective regulation of international trade in UEEE from both exporting and importing countries. Although, the export of e-waste from the European Community to developing countries is currently prohibited, significant amount of e-waste from the region continue to flow into developing countries due to lax regulatory measures in the latter. Hence, there is need for a regulatory regime in developing countries to complement the prohibitory regime in the major e-waste source countries. This paper proposes trade measures modelled in line with WTO rules which could be adopted by developing countries in addressing these problems. The proposed measures include the development of a compulsory certification and labelling system for functional UEEE as well as trade ban on commercial importation of UEEE not complying with the said certification and labelling system. The paper then goes further to examine these proposed measures in the light of WTO rules and jurisprudence.